Regularização fundiária de assentamentos urbanos informais: fator de fixação de população de baixa renda ou promoção do mercado imobiliário formal? o caso do Assentamento Bengui - Etapa 2, Belém-PA - SILVA, Maria do Carmo Campos da (Universidade Federal do Pará, 2019)
This study deals with the urban land regularization of social interest, which as a public policy aims to guarantee the social right to housing, through the adoption of legal, urban, social and environmental measures for predominantly low-income families that informally occupy urban spaces. The research was carried out in the informal urban settlement called Bengui - Etapa 2 located in the Bengui neighborhood, which was subject to land regularization in 2013 Programa Municipal de Regularização Fundiária do Município de Belém “Chão Legal”. The study analyzed whether these actions contributed to the permanence of families in the regularized settlement or if they only made it possible to enter new lots in the formal real estate market. The research combined evidence of quantitative and qualitative orders, and identified that of the 287 regularized lots, the number of families that remained after regularization was above ninety per cent. Through interviews it was obtained the point of view of the residents as to the factors that contribute to the families that have had their regularized properties remain or abandon the settlement after land regularization, as well as the factors that induce other people to seek this area as a place of residence. A brief analysis was also carried out on the real estate valuation in the settlement and in the Bengui neighborhood under the perspective of appropriation of this valuation by the real estate market, by the municipality and by the residents. For the residents of the Bengui-Step 2 settlement, the location of real estate, which favors access to the various services used in their daily lives, is the most relevant factor for the permanence of the families in the place, and as complementary factors related: the existing infrastructure at local level even if it does not meet all of their needs, the already established support links in the area and the security they attribute to the titling of their property against possible threats of eviction, as occurs in areas not regularized in the name of the occupants. Despite recognizing the appreciation of real estate arising from land regularization, they were not likely to dispose of their regularized lots